Before fanfiction : recovering the literary history of American media fandom - Edwards, Alexandra (Writing instructor) (Louisiana State University Press, 2023)
"Fan studies has a literary history problem. From the discipline's seminal works of the early 1990s to its recent, media-attention-garnering popular scholarship, fan studies has repeated one creation myth time and again. "Fandom," this myth tells us, might have gained popularity in the 1960s as female audiences mimeographed and mailed each other Star Trek fanzines, but it owes its creation to the male-dominated world of the 1930s science fiction pulps. But this history neglects the full picture of U.S. fan cultures in the early twentieth century, and it erases the many women writers and readers who transformed American culture by their participation in early forms of fandom. Before Fanfiction serves as an intervention. It examines the work of popular women writers working in "middlebrow," modernist, and regional forms, and the fan responses to such work, in order to present a counter-history of fan cultures - one that returns women to center stage, while arguing for a more complex, less hierarchical understanding of authorship, genre, and the American literary marketplace in early twentieth century. This book is the first to approach early twentieth-century fan culture from a literary-historical perspective. It will appeal to both literature and fan studies scholars, who will find in it not only research and analysis but also a model for future work examining the many connections between literature and fan culture"-- Provided by publisher.
Keywords: American literature -- Women authors -- Appreciation.; American literature -- 20th century -- Appreciation.; Popular literature -- United States -- History and criticism.; Fans (Persons) -- United States -- History -- 20th century.; Fan fiction -- History and criticism.; Literature and society -- United States -- History -- 20th century.; Écrits de femmes américains -- Appréciation.; Littérature américaine -- 20e siècle -- Appréciation.; Paralittérature -- États-Unis -- Histoire et critique.; Fanfiction -- Histoire et critique.; Littérature et société -- États-Unis -- Histoire -- 20e siècle.; American literature -- Appreciation; Fan fiction; Fans (Persons); Literature and society; Popular literature; United States; 1900-1999; Electronic books.; Criticism, interpretation, etc.; History; Literary criticism; Literary criticism.; Critiques littéraires.